Locations and mucosal lesions responsible for major gastrointestinal bleeding in patients on warfarin or dabigatran - Kolb, Jennifer; Brückmann, Martina (Digestive diseases and sciences, 2018)
Different oral anticoagulants may be associated with gastrointestinal bleeding (GIB) from different locations or mucosal lesions. We aimed to test this hypothesis.
Gesehen am 10.12.2019